Strategi Pengembangan Bisnis dengan Pendekatan Business Model Canvas pada Usaha Rumah Makan Dapur Mandar: Penelitian - Sahrul Salam; Rizki Abdillah Tanjung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the business model, map customer needs, formulate strategic alternatives, prioritize the best strategic alternatives, and design a new business model using the Business Model Canvas approach. The study was conducted at Usaha Rumah Makan Dpaur Mandar using qualitative research as the primary method and quantitative research as a supporting method. Data collection was carried out through interviews, observations, documentation, and questionnaires. The Business Model Canvas was used to describe the current business model, empathy map analysis to identify and map customer needs, SWOT analysis to formulate strategic alternatives, and QSPM matrix to determine the priority of strategies. The SWOT analysis produced eight strategic alternatives, including: 1) Opening new branches, 2) Maintaining food quality, 3) Partnering with delivery services, 4) Aggressive promotions, 5) Collaboration with influencers, 6) Offering package promotions, 7) Introducing new menus, 8) Improving customer service. Based on the QSPM matrix, the strategy of maintaining food quality with the highest Total Attractiveness Score (TAS) of 7.0743 was determined.